2008
DOI: 10.1111/j.1467-6494.2007.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Values: Family Generativity and Adolescents' Narratives of Parent and Grandparent Value Teaching

Abstract: In this longitudinal study, we compared family stories told by 32 Canadian adolescents at ages 16 and 20 about how parents and grandparents had taught them values. Relations to parents' and children's levels of generativity were also examined. Adolescents' stories of grandparent value teaching were less readily recalled and less interactive in their content compared with stories about parents. Stories of value teaching by more generative parents were more likely to involve specific episodes, to be more interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 21 publications
3
25
0
2
Order By: Relevance
“…Revisiting family pleas: Generativity assumes that conversations 'live on' and people revisit their experiences and exchanges within the familial or broader relational domain. It is a site for 'constant negotiation' where the conceptions of self evolves during a lifespan (Pratt et al, 2008). Returning to the appeals of his deceased grandparents, one calling-oriented participant recounted how he perceived their explicit plea as inspirational, which acted as a driving force to pursue medicine:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Revisiting family pleas: Generativity assumes that conversations 'live on' and people revisit their experiences and exchanges within the familial or broader relational domain. It is a site for 'constant negotiation' where the conceptions of self evolves during a lifespan (Pratt et al, 2008). Returning to the appeals of his deceased grandparents, one calling-oriented participant recounted how he perceived their explicit plea as inspirational, which acted as a driving force to pursue medicine:…”
Section: Resultsmentioning
confidence: 99%
“…For example, a longitudinal study by Pratt, Norris, Hebblethwaite, and Arnold (2008) found that a greater number of life interventions by more generative parents were associated with greater adolescent acceptance of conveyed value messages. Family culture and communication can therefore form an important element in vocational socialization (Jablin, 2001).…”
Section: Literature Overview Callingsmentioning
confidence: 99%
“…Portanto, a satisfação das mães quanto ao envolvimento paterno durante a sua gravidez e o nascimento dos filhos depende, também, da própria dinâmica familiar existente antes mesmo destes se tornarem pais. Além disso, deve ser considerado como fonte de influência as relações estabelecidas pelo casal com seus respectivos genitores, pois eles desempenham papéis significativos nas expectativas e realizações quanto ao papel parental (Pratt, Norris, Hebblethwaite, & Arnold, 2008).…”
Section: Discussionunclassified
“…In this vein, the classical Eriksonian model, which links life interests to specific chronological periods, has been questioned as both too rigid and too simple (Villar, 2012). In the case of generativity, this would mean that generative concerns and behaviors could appear in young adulthood (e.g., Pratt, Norris, Hebblethwaite & Arnold, 2008) and, particularly, that they can persist beyond middle adulthood.…”
Section: Generativity: An Intrinsically Intergenerational Conceptmentioning
confidence: 96%